2009
DOI: 10.2460/javma.234.6.794
|View full text |Cite
|
Sign up to set email alerts
|

Degenerative disease of the distal interphalangeal joint and sesamoid bone in calves: 9 cases (1995–2004)

Abstract: Degenerative disease of the DIJ should be considered in calves with insidious, progressive forelimb lameness. Although the etiology of this process remains undetermined, results of radiographic, computed tomographic, and histologic examinations suggested an underlying developmental anomaly, such as osteochondrosis. Surgical treatment appeared promising on the basis of postoperative resolution of lameness in all surgically treated calves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…In another retrospective study, the occurrence of DJD was reported in the interphalangeal joint and in the sesamoid bone in calves (Mulon et al 2009). The degree of erosion of the articular cartilage varies with age, inflammation stage and mechanical factors (Shupe 1961).…”
Section: Discussionmentioning
confidence: 98%
“…In another retrospective study, the occurrence of DJD was reported in the interphalangeal joint and in the sesamoid bone in calves (Mulon et al 2009). The degree of erosion of the articular cartilage varies with age, inflammation stage and mechanical factors (Shupe 1961).…”
Section: Discussionmentioning
confidence: 98%
“…Concurrent secondary degenerative joint disease was observed in seven joints and this study could not corroborate the link between OC and degenerative joint disease. However, previous reports in cattle have indicated a strong developmental relationship between these two diseases [2,13,22]. Radiographic grading findings suggested that a grade 1/ grade 3 case and a grade 4 case with coexisting degenerative joint disease were sent to slaughter in comparison to grade 1 case, grade 2 cases and a grade 4 case with degenerative joint disease.…”
Section: Discussionmentioning
confidence: 95%
“…Computed tomography (CT) is not routinely utilized in cattle due to economic constraints. Although it is uncommon to diagnose OC by CT so far, it can be a potential tool to visualize the existence and the degree of OC lesion in calves with unknown lameness according to a previous report showing its usefulness in degenerative joint disease in female calves [13]. The study suggested that the use of CT gave better understanding of changes in the bones.…”
Section: Discussionmentioning
confidence: 95%